Aplikasi Safe Travel dalam Mempengaruhi Keputusan Pengguna Berwisata ke Luar Negeri - Anggi Khoirunnisa; Devi Roza K. Kausar; Yustisia P. Mbulu (Journal of Tourism Destination and Attraction, 2017)
The Safe Travel app is an application developed by the Ministry of Foreign Affairs of the Republic of Indonesia, which contains practical information to assist Indonesian citizens when they are abroad. The application also gives suggestions and warnings regarding the country that the users are in, to ensure their safety whilst on the trip. Using tourism mobile application concept, the purpose of this research is to describe the features of Safe Travel app and investigate how the application influences the decision to travel among its users. The study used survey as means for data collection method and 60 respondents participated in the survey. Multiple linear regression was used to analyse the data collected. The findings indicate that navigation, social communication, marketing, emergency, transactions and entertainment variable do not influence the decision to travel abroad. Meanwhile, information variable has a positive effect on the decision to travel.